2006
DOI: 10.4049/jimmunol.176.9.5652
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 and NF-κB Signal Pathway Is Required for IL-23-Mediated IL-17 Production in Spontaneous Arthritis Animal Model IL-1 Receptor Antagonist-Deficient Mice

Abstract: IL-23 is a heterodimeric cytokine composed of a p19 subunit and the p40 subunit of IL-12. IL-23 has proinflammatory activity, inducing IL-17 secretion from activated CD4+ T cells and stimulating the proliferation of memory CD4+ T cells. We investigated the pathogenic role of IL-23 in CD4+ T cells in mice lacking the IL-1R antagonist (IL-1Ra−/−), an animal model of spontaneous arthritis. IL-23 was strongly expressed in the inflamed joints of IL-1Ra−/− mice. Recombinant adenovirus expressing mouse IL-23 (rAd/mIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
196
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(207 citation statements)
references
References 53 publications
(56 reference statements)
8
196
1
Order By: Relevance
“…Phosphorylations of STAT1 and STAT3 at the Tyr701 or Tyr705 residues, respectively, induce their dimerization, nuclear translocation, and DNA binding [6,17]. In our study, IL-27 alone induced tyrosine phosphorylation of STAT1 (Fig.…”
Section: Expression Of Il-12 Il-23 and Il-27 Receptor Subunits In Hsupporting
confidence: 58%
See 3 more Smart Citations
“…Phosphorylations of STAT1 and STAT3 at the Tyr701 or Tyr705 residues, respectively, induce their dimerization, nuclear translocation, and DNA binding [6,17]. In our study, IL-27 alone induced tyrosine phosphorylation of STAT1 (Fig.…”
Section: Expression Of Il-12 Il-23 and Il-27 Receptor Subunits In Hsupporting
confidence: 58%
“…It has been reported that IL-12 and IL-23 activate NF-jB in DC and memory CD4 + T cells, respectively [6,23]. In these cells, JAK2 is involved in the activation of NF-jB; JAK2 may activate IKK via the downstream pathways PI3K/Akt [24,25] and/or PKC/c-src [26].…”
Section: Expression Of Il-12 Il-23 and Il-27 Receptor Subunits In Hmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Binding of IL-23 to its receptor activates STAT3 and IL-17 production is then induced. [10][11][12][13] Recently, a small number of IL23R splice variants were identified in normal lymphoid cell lines and human tumor cells. 14 This study was recently independently confirmed (Kan et al, personal communication) and together these recent publications describe exon deletion splice variants of the human IL-23 receptor complex.…”
mentioning
confidence: 99%